2022
DOI: 10.3389/fphar.2022.1041915
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between adenoma detection rate and other quality indicators, and its variability depending on factors such as sedation or indication for colonoscopy

Abstract: Colorectal cancer (CRC) is an important worldwide public health burden and colonoscopy is the main diagnostic and most importantly, preventive method. For this reason, many countries have implemented national or regional CRC screening programs. High-quality colonoscopy is a prerequisite to effectively detect premalignant lesions, like adenomas. The quality of colonoscopy is assessed using several quality indicators, the main one being adenoma detection rate (ADR). In Romania, despite CRC having the highest inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…17 Some findings even indicated that ADR and PDR may be higher with general endoscopy without anesthesia. 25 In the present study, it was found that sedated endoscopy improved the ADR, AADR and PDR, suggesting that sedation can help enhance the diagnostic ability of colonoscopy. Thus, sedation should be considered as a potential quality influencing factor.…”
Section: Discussionsupporting
confidence: 54%
“…17 Some findings even indicated that ADR and PDR may be higher with general endoscopy without anesthesia. 25 In the present study, it was found that sedated endoscopy improved the ADR, AADR and PDR, suggesting that sedation can help enhance the diagnostic ability of colonoscopy. Thus, sedation should be considered as a potential quality influencing factor.…”
Section: Discussionsupporting
confidence: 54%